Ahlul Bait Dalam Puisi-Puisi Penyair Keturunan Bani Umayyah: Studi Historis dan Kritik Sastra Atas Karya Abu Adiy al-Umawi, Marwan as-Saruji dan Al-Abiwardi - Irfanullah, Gumilar; Anggraeni, Dewi; Agustina, Ina (IAIN Syekh Nurjati Cirebon, 2023)
This article traces the names of poets who came from the Umayyad lineagebut had an attitude that was the opposite of that family towards the Ahlul Bait(prophet's family: Ali, Fatimah, Hasan and Husain). In Islamic historicalrecords, the majority of the Umayyads were socially and politically showedresistance and opposition to the Prophet Muhammad and his descendants, butthere were several names from the Umayyad clan who were exceptions andactually went against the traditions of their group. To study it, this article usesa historical approach and literary criticism towards several poets descended from the Umayyads and several verses of their poetry about the Ahlul Bait. At that time, poetry could function as a socio-political identity and expressionfor a poet to describe his world. Based on the theory of neo-historicism, this article tries to explore the cultural context behind the poetic texts originating from these poets to understand the socio-political conditions at that time as well as the tendencies of their political and religious tendencies.